2018
DOI: 10.1016/j.ebiom.2018.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Lnc-PCDH9-13:1 Is a Hypersensitive and Specific Biomarker for Early Hepatocellular Carcinoma

Abstract: BackgroundLong non-coding RNAs (lncRNAs) show great potential as diagnostic tools in many diseases. We aimed to develop sensitive and noninvasive biomarkers in saliva for detecting early hepatocellular carcinoma (HCC).MethodsCandidate lncRNA biomarkers identified by Agilent microarray were subjected to validation using qPCR for the quantification of their expression levels in independent tissue, plasma and saliva sample sets, including healthy controls, HBsAg carriers, patients with chronic Hepatitis B, liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 29 publications
6
40
0
Order By: Relevance
“…MiR-494-3p as a carcinogenic factor was upregulated in lung cancer and promoted the progression of lung cancer ( 21 ). Based on the competing endogenous RNA (ceRNA) hypothesis and the fact that LINC00355 acts as a carcinogenic factor in several cancers ( 15 18 ), miR-466 was thus selected for the following analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-494-3p as a carcinogenic factor was upregulated in lung cancer and promoted the progression of lung cancer ( 21 ). Based on the competing endogenous RNA (ceRNA) hypothesis and the fact that LINC00355 acts as a carcinogenic factor in several cancers ( 15 18 ), miR-466 was thus selected for the following analysis.…”
Section: Methodsmentioning
confidence: 99%
“…It has no protein-coding capacity, and can interact with chromatin and histone modifiers, thereby regulate gene expression ( 14 ). Several reports suggest that the abnormal expression of LINC00355 is linked to the overall survival of cancers such as prostate cancer, colorectal cancer, and colon adenocarcinoma ( 15 18 ). LINC00355 is regarded as a good candidate for understanding the mechanisms of sepsis ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the investigation and recognition of lncRNAs, there is increasing evidence that they have significant roles as tumor oncogenes or/and suppressors (8)(9)(10). Furthermore, several lncRNAs are important in the progression and development of liver cancer (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that PCDH9 was down-regulated in cancers, such as glioblastoma, hepatocellular carcinoma and gastric cancer. [35][36][37][38] Overexpression of PCDH9 inhibited the proliferation, migration and invasion of cancer cells. However, the function of PCDH9 in ovarian cancer remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%